1987
DOI: 10.1111/j.1748-1716.1987.tb08087.x
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of central β‐adrenoceptors attenuates tremor induced by 5‐hydroxytryptamine (5‐HT)‐receptor activation in rats

Abstract: The effect of beta-adrenoceptor antagonists, varying in lipophilicity and receptor selectivity, were studied on tremor elicited by L-5-hydroxytryptophan (L-5-HTP) in rats pretreated with a peripherally acting decarboxylase inhibitor and a monoamine oxidase inhibitor, or by the directly acting 5-HT agonist 5-methoxy-N,N-dimethyltryptamine (5-MeODMT). Plasma levels of the beta-adrenoceptor antagonists were determined simultaneously. The non-selective lipophilic adrenoceptor antagonist propranolol was found to do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…142 Tremor in rats is attenuated after blockage of centrally located ␤ 2 -adrenoceptors. 143 Occurrence of tremor in cats after intracaudate injection of amphetamines, 144 mescaline, tetrabenazine, bretylium, 145 or morphine 146 has been reported. Serotonin depletion and blockage of 5-HT receptors but not catecholamine depletion prevents the amphetamine syndrome in rats; for that reason, Sloviter et al suggest that it is mediated through activated 5-HT receptors.…”
Section: Miscellaneous Tremorogensmentioning
confidence: 99%
“…142 Tremor in rats is attenuated after blockage of centrally located ␤ 2 -adrenoceptors. 143 Occurrence of tremor in cats after intracaudate injection of amphetamines, 144 mescaline, tetrabenazine, bretylium, 145 or morphine 146 has been reported. Serotonin depletion and blockage of 5-HT receptors but not catecholamine depletion prevents the amphetamine syndrome in rats; for that reason, Sloviter et al suggest that it is mediated through activated 5-HT receptors.…”
Section: Miscellaneous Tremorogensmentioning
confidence: 99%
“…The latter drug has also found a clinical use in the treatment of migraine (Anthony, 1978;Weber & Reinmuth, 1972) and anxiety states (Heiser & DeFrancisco, 1976;Linken, 1971 (Young et al, 1975;Taylor et al, 1981;Kuroda et al, 1988) an interference with 5-HT systems may be important (Hallberg, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…It remains unclear, however, whether any of these effects of propranolol are due to actions at fl-adrenoceptors or whether other receptor populations are involved with an intermediate situation on pathways involved in the control of tremor and cerebrovascular tone. While it has been proposed that antagonism of fl-adrenoceptors is involved in the antitremor activity (Young et al, 1975;Taylor et al, 1981;Kuroda et al, 1988) an interference with 5-HT systems may be important (Hallberg, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Ablad et al. 1973, Borg et al 1975, Hallberg 1987. Thus, the effect appears to be mediated by blockade of P,-adrenoceptors rather than P,-adrenoceptors, a notion given further support by the reduction in tremor found in rats treated with the lipophilic P,-antagonist ICI 118, 551 (Bilski et al 1983) (calculated distribution coefficient 95, P. Johansson, pers.…”
Section: Plasma Concentrations Of P-antagonistsmentioning
confidence: 97%
“…In a recent study by Ogren et al (1985), alaproclate, a 5-HT-uptake inhibitor, was found to potentiate oxotremorine-induced tremor in rats, suggesting that a serotonergic mechanism participates in this kind of tremor. Since tremor induced by activation of central 5-HT-systems also appears to be modulated by central P,-adrenoceptors (Hallberg 1986(Hallberg , 1987, it is tempting to suggest that centrally located /I,-adrenoceptors may modulate a mechanism that is common to the tremor models studied.…”
Section: Plasma Concentrations Of P-antagonistsmentioning
confidence: 99%